Parallel evolution of two distinct lymphoid proliferations in clonal haematopoiesis. Issue 5 (1st March 2022) - Attygalle, Ayoma D; Dobson, Rachel; Chak, Pui Kwan; Vroobel, Katherine M; Wren, Dorte; Mugalaasi, Hood; Morgan, Yvonne; Kaur, Manmit; Ahmad, Raida; Chen, Zi; Naresh, Kikkeri N; Du, Ming‐Qing
Abstract : Aims: Angioimmunoblastic T‐cell lymphoma (AITL) is genetically characterized by TET2 and DNMT3A mutations occurring in haematopoietic progenitor cells, and late events (e.g. the RHOA ‐G17V mutation) associated with malignant transformation. As TET2 / DNMT3A ‐mutated progenitor cells can differentiate into multilineage progenies and give rise to both AITL and myeloid neoplasms, they may also have the potential to lead to other metachronous/synchronous neoplasms. We report two cases showing parallel evolution of two distinct potentially neoplastic lymphoid proliferations from a common mutated haematopoietic progenitor cell population. Methods and results: Both cases presented with generalized lymphadenopathy. In case 1 (a 67‐year‐old female), an initial lymph node (LN) biopsy was dismissed as reactive, but a repeat biopsy showed a nodal marginal zone lymphoma (NMZL)‐like proliferation with an increase in the number of T‐follicular helper (TFH) cells. Immunohistochemistry, and clonality and mutational analyses by targeted sequencing of both whole tissue sections and microdissected NMZL‐like lesions, demonstrated a clonal B‐cell proliferation that harboured the BRAF ‐G469R mutation and shared TET2 and DNMT3A mutations with an underlying RHOA‐ G17V‐mutant TFH proliferation. Review of the original LN biopsy showed histological and immunophenotypic features of AITL. In case 2 (a 66‐year‐old male), cytotoxic T‐cell lymphoma with an increase in the number of Epstein–Barr virus‐positive large B cells was diagnosed on initial biopsy. On review together with the relapsed biopsy, we identified an additional occult neoplastic TFH proliferation/smouldering AITL. Both T‐cell proliferations shared TET2 and DNMT3A mutations while RHOA ‐G17V was confined to the smouldering AITL. Conclusions: In addition to demonstrating diagnostic challenges, these cases expand the potential of clonal haematopoiesis in the development of different lineage neoplastic proliferations. Abstract : Two unique cases show parallel evolution of distinct lymphoid neoplasms from a common TET2/DNMT3A mutated haematopoietic progenitor. In case 1, an EBV‐negative clonal B‐cell proliferation mimicking nodal marginal zone B‐cell lymphoma (NMZL) obscured an underlying angioimmunoblastic T cell lymphoma (AITL). In case 2, a predominant CD8+ cytotoxic T‐cell proliferation/lymphoma concealed an occult neoplastic T‐helper cell proliferation/smouldering AITL.